Building Information Modelling (BIM): A Narrative Literature Review on Theory, Benefits, and Barriers - Jalaludin (Journal Innovation of Civil Engineering (JICE), 2025)
Building Information Modelling (BIM) has emerged as a transformative methodology within the Architecture, Engineering, and Construction (AEC) sector, significantly changing the approach to project planning, execution, and management. This study presents a narrative literature review (NLR) of BIM, focusing on its theoretical foundations, implementation benefits, and the key barriers to its adoption. The objective is to identify and synthesize the core concepts that define BIM's maturity levels, level of development (LOD), and the use of a common data environment (CDE) within the construction industry. The literature search was conducted using Google Scholar, with keywords such as "Building Information Modelling," "BIM benefits," "BIM barriers," and "BIM theory." The findings indicate that BIM offers significant advantages in enhancing design quality, facilitating collaboration, improving cost estimation, promoting sustainability, and optimizing lifecycle management. However, its implementation faces challenges, including high initial investment, lack of skilled professionals, interoperability issues, and organizational resistance. A case study on a residential building project was also included to illustrate the practical application of 3D, 4D, and 5D BIM. This review concludes with recommendations to enhance BIM adoption through standardization, training, supportive policies, and promoting its role in sustainable construction. Keywords: Narrative Literature Review (NRL); BIM maturity; Level of Development (LOD); Common Data Environment (CDE); BIM barriers.